In the Name of Humanitarianism: The Interim Federal Health Program and the Irregularization of Refugee Claimants - Connoy, Laura (Refuge, 2018)
Since 1957 Canada’s Interim Federal Health Program (IFHP) has provided health-care coverage to refugee populations. However, from June 2012 to April 2016 the program was drastically revised in ways that restricted or denied access to health-care coverage, specifically to refugee claimants—persons who have fed their country and made an asylum claim in another country. One of the main intentions of the revision was to protect the integrity of Canada’s humanitarian refugee determination system. However, this had a major unintended consequence: within everyday healthcare places like walk-in clinics, doctor’s offices, and hospitals, IFHP recipients were denied access to services, regardless of actual levels of coverage. In this article I analyze how these program restrictions were experienced within Toronto’s everyday health-care places through the concept of irregularization. I discuss how the IFHP, as a humanitarian health-care program, problematizes the presence of refugee claimants in ways that created experiences of vulnerability, insecurity, and anxiety. Building on this view, I conclude with a discussion of how activists who sought to draw attention to the experiences of refugee claimants in the aftermath of the IFHP revisions closed of truly transformative pathways toward social justice.